Nursery cultivation regimes, plant functional attributes, and field performance relationships in the Mediterranean oak Quercus ilex L. - VILLAR-SALVADOR, P; Planelles, R; Enrı́quez, E; Rubira, J.Peñuelas (Forest Ecology and Management, 2004)
In this study we have addressed the effect of nitrogen fertilisation and shading used during nursery growth on the functional quality of Quercus ilex L. (holm oak) seedlings and their outplanting performance in an abandoned continental Mediterranean cropland. Three N fertilisation regimes: high and low fertilisation (154 and 34 mg N per plant, respectively) and no fertilisation, combined with two shade levels (full sun and 45% shade) were studied. Fertilisation increased the shoot size, shoot to root mass ratio (S/R), root N, and both shoot and root P concentration of the plants produced in the nursery. Fertilisation also enhanced the capacity of new root formation. Neither tissue K nor root mass was affected by N fertilisation. Shading increased S/R and root K concentration but reduced both shoot and root N concentration. Two years after planting, unfertilised seedlings had higher mortality and grew signiﬁcantly less than those cultivated at both a low and a high fertilisation level. Shading during nursery growth had no inﬂuence on the outplanting performance of holm oak seedlings. Plants with a larger shoot and higher S/R had lower mortality and grew faster than those with a smaller shoot and lower S/R. Outplanting performance of holm oak seedlings was related with root N and P concentration and with RGC. No relationship was found with either shoot nutrient concentration or root mass. We conclude that high N fertilisation of holm oak seedlings in the nursery can improve their early ﬁeld establishment in the afforestation Mediterranean abandoned croplands.
Keywords: Afforestation; Holm oak; nitrogen; nursery fertilisation; root growth capacity; shading

Nursery cultivation regimes, plant functional attributes, and field performance relationships in the Mediterranean oak Quercus ilex L. - Villar-Salvador, P.; Planelles, R.; Enrı́quez, E.; Rubira, J. Peñuelas (Forest Ecology and Management, 2004)
In this study we have addressed the effect of nitrogen fertilisation and shading used during nursery growth on the functional quality of Quercus ilex L. (holm oak) seedlings and their outplanting performance in an abandoned continental Mediterranean cropland. Three N fertilisation regimes: high and low fertilisation (154 and 34 mg N per plant, respectively) and no fertilisation, combined with two shade levels (full sun and 45% shade) were studied. Fertilisation increased the shoot size, shoot to root mass ratio (S/R), root N, and both shoot and root P concentration of the plants produced in the nursery. Fertilisation also enhanced the capacity of new root formation. Neither tissue K nor root mass was affected by N fertilisation. Shading increased S/R and root K concentration but reduced both shoot and root N concentration. Two years after planting, unfertilised seedlings had higher mortality and grew signiﬁcantly less than those cultivated at both a low and a high fertilisation level. Shading during nursery growth had no inﬂuence on the outplanting performance of holm oak seedlings. Plants with a larger shoot and higher S/R had lower mortality and grew faster than those with a smaller shoot and lower S/R. Outplanting performance of holm oak seedlings was related with root N and P concentration and with RGC. No relationship was found with either shoot nutrient concentration or root mass. We conclude that high N fertilisation of holm oak seedlings in the nursery can improve their early ﬁeld establishment in the afforestation Mediterranean abandoned croplands.
Keywords: Afforestation; Holm oak; nitrogen; nursery fertilisation; root growth capacity; shading